Collisional history of asteroid Itokawa - Jourdan, Fred; Timms, Nicholas Eric; Eroglu, Ela; Mayers, C.; Frew, A.; Bland, Phil; Collins, G.; Davison, T.; Abe, M.; Yada, T. (Geological Society of America, 2017)
In situ extraterrestrial samples returned for study (e.g., from the Moon) are crucial in understanding the origin and evolution of the Solar System as, contrary to meteorites, they provide a known geological context for the samples and their analyses. Asteroid 25143 Itokawa is a rubble-pile asteroid consisting of reaccumulated fragments from a catastrophically disrupted monolithic parent asteroid, and from which regolith dust particles have been recovered by the Hayabusa space probe (Japan Aerospace Exploration Agency). We analyzed two dust particles using electron backscatter diffraction and 40 Ar/ 39 Ar dating techniques. One of the grains, showing signs of 15-25 GPa impact shock pressure, yielded a 40 Ar/ 39 Ar plateau age of 2.3 ± 0.1 Ga. We developed a novel temperature-pressure-porosity model, coupled with diffusion models to show that the relatively low pressure and high temperature involved in the impact process can be reconciled only if the asteroid was already made of porous material at ca. 2.3 Ga and, thus, if asteroid Itokawa was already formed, thereby providing a minimum age for catastrophic asteroid breakup. A second particle shows no sign of deformation, indicating shock pressure of < 10 GPa and a calculated maximum temperature of ~200 °C. This low temperature estimate is compatible with a lack of isotopic resetting for this particle. This suggests that the breakup of Itokawa's parent was a relatively low-temperature process at the scale of the asteroid, and occurred on a pre-shattered parent body.